Resilient Europe: European public opinion and Euroscepticism or how things might be different from what we believe - Losada, Antón; Maneiro, Elba (Política y Sociedad, 2021)
In the last decade, and with Brexit as a turning point, discontent and mistrust of the EU institutions as well as the rise of Eurosceptic political forces have called into question both the legitimacy of the EU integration process and the common European identity. In this context, there are many voices that assume that this growth of political parties of a Eurosceptic or even anti-EU nature goes hand in hand with a loss of identification with the European project. In this article, however, we question whether the rise of these political formations has been paralleled by a decline in the sense of EU membership and identification of European citizens as such. To contrast our hypothesis, we analyze different time series on key questions about EU identity and competences from the Eurobarometer Standard carried out by the European Commission. Data is provided to support the hypothesis of the consolidation of a dual identity of European citizens, a perspective in which national identity, regional identity and European identity do not necessarily compete with each other, but in which citizens build their identity in a complementary way.